From Shopping to Statistics: Tracking and Nowcasting Private Consumption Expenditures in Real-Time - Friederike Fourné; Robert Lehmann (Center for Economic Studies and ifo Institute (CESifo), 2023)
In this paper, we use high-frequency transaction data to develop a weekly tracker for private consumption expenditures. Furthermore, we apply the transaction data in a nowcasting experiment and compare their performance with other, readily available indicators that are regularly linked to private consumption in Germany. The weekly tracker produces precise estimates and can thus be used in real-time, especially in very turbulent times such as a pandemic or the high-inflation-phase in its aftermath. In terms of nowcast accuracy, the tracker outperforms all remaining indicators, making it a powerful tool for applied forecasting work. We plan to regularly publish the weekly consumption tracker in the future, thereby complementing the database for Germany.
Keywords: C32; C53; E01; E21; E27; 330; private consumption expenditures; real-time tracker; high-frequency transaction data; mixed-frequency vectorautoregression; Bayesian estimation